Nrf2 Activators as Dietary Phytochemicals Against Oxidative Stress, Inflammation, and Mitochondrial Dysfunction in Autism Spectrum Disorders: A Systematic Review - Yang, Jiaxin; Fu, Xi; Liao, Xiaoli; Li, Yamin (Frontiers in Psychiatry, 2020)
Autism spectrum disorder (ASD) is a pervasive neurodevelopmental disorder with limited available treatments and diverse causes. In ASD patients, numerous researches demonstrated various alterations in inflammation/immune, oxidative stress, and mitochondrial dysfunction, and these alterations could be regulated by Nrf2. Hence, we aimed to systematically review the current evidence about the effects of Nrf2 activator supplementation on ASD objects from in vitro studies, animal studies, and clinical studies. Relevant articles were retrieved through searching for the Cochrane Library, PubMed, Web of Science, Scope, Embase, and CNKI databases (through September 23, 2020). Ultimately, we identified 22 preclinical studies, one cell culture study, and seven clinical studies, covering a total of five Nrf2 activators. For each Nrf2 activator, we focused on its definition, potential therapeutic mechanisms, latest research progress, research limitations, and future development directions. Our systematic review provided suggestive evidence that Nrf2 activators have a potentially beneficial role in improving autism-like behaviors and abnormal molecular alterations through oxidant stress, inflammation, and mitochondrial dysfunction. These dietary phytochemicals are thought to be relatively safer and effective for ASD treatment. However, there are few clinical studies to support the Nrf2 activators as dietary phytochemicals in ASD, even though several preclinical studies. Therefore, caution should be warranted in attempting to extrapolate their effects in human studies, and better design and more rigorous research are required before they can be determined as a therapeutic option.